2009
DOI: 10.1089/acm.2009.0065
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Differentiation in Traditional Chinese Medicine Can Help Define Specific Indications for Biomedical Therapy in the Treatment of Rheumatoid Arthritis

Abstract: TCM pattern differentiation based on symptoms can help identify a subset of patients with RA that will more likely respond to biomedical therapy, consisting of diclofenac, methotrexate, and sulfasalazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 8 publications
3
52
0
Order By: Relevance
“…pain, swelling and deformation), which are included in RA diagnosis in biomedicine; cold feeling in joints and pain relieved with warming, which are important for TCM cold pattern differentiation; and hot feeling and pain relieved with cooling, which are important for TCM hot pattern differentiation [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…pain, swelling and deformation), which are included in RA diagnosis in biomedicine; cold feeling in joints and pain relieved with warming, which are important for TCM cold pattern differentiation; and hot feeling and pain relieved with cooling, which are important for TCM hot pattern differentiation [6].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the clinical manifestations, the patients with RA could be classified into different patterns under traditional Chinese medicine (TCM); these TCM patterns can help find a subset of RA patients for a specific type of therapy [5,6]. The diversified clinical manifestations must be a consequence of biological networks comprising hundreds of thousands of gene expressions changed in various affected tissues and immune effector cells [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of CRP, as demonstrated in patients with RA, can contribute to disease progression (Pasceri et al, 2001;Vogt et al, 2007). CRP was proved to be correlated with pattern classification based on TCM theory according to our prior study (Lu et al, 2009), the level of CRP was significantly lower in the patients with CM cold pattern than in those with CM hot pattern (more patients with cold pattern show normal level of CRP). Moreover, the effect rate according to ACR20 response in WM drugs group was higher in patients with cold pattern than in those with hot pattern (He et al, 2008).…”
Section: Figmentioning
confidence: 81%
“…6, CRP in normal scale and dizziness were detected as risk factors of GI ADRs in this study. In our previous study, we found that GI ADRs were negatively correlated with curative effect (Ji, and CRP was negatively correlated with TCM cold pattern in RA patients (Lu et al, 2009), and WM treatment were better in the treatment of RA with TCM cold pattern (He et al, 2008). As a TCM symptom, dizziness also belonged to the factor which represented the deficient pattern, as the same with lassitude and nocturia (He et al, 2008).…”
Section: Figmentioning
confidence: 91%